Comparative analysis of efficacy and safety of transurethral and vesicoscopic surgery of primary vesicoureteral reflux in children - A. V. Pirogov; V. V. Sizonov; M. I. Kogan (Вестник урологии, 2020)
Introduction. Research interest in vesicoureteral reflux (VUR) is determined by continued dissatisfaction with the treatment results, which do not exclude the development of renal failure and hypertension. The management tactics of such patients currently range from the dynamic follow-up to various surgical correction options, which determines the relevance of developing a personalized approach when choosing a surgical treatment technique.Purpose of the study. The study was aimed at a comparative analysis of the efficacy and safety of transurethral administration of a polyacrylate polyalcohol copolymer (PPC) and vesicoscopic transregional ureterovesical anastomosis (VUVA) according to Cohen.Materials and methods. The study is based on a retrospective analysis of the results of treatment of 214 patients with primary VUR, who underwent surgery from 2012 to 2018. The average age was 61.7 ± 47.9 months. Girls — 133 (62.1%), boys — 81 (37.6%). Indication for surgery in 150 (70%) children was recurrent urinary tract infection, in 64 (30%) — progressive reflux nephropathy. Bilateral process was observed in 92 (43%) patients, left-sided — in 69 (32%), right-sided — in 53 (25%). Patients were divided into two groups. Group I — 119 (55.6%) patients (179 renal units (RU)), who underwent endoscopic treatment (ET) using PPC. Group II — 95 (44.4%) children (127 RU) who underwent VUVA. Each of the groups was divided into subgroups, including RU with a low grade of (I-III) VUR and RU with a high grade of (IV-V) VUR. Complications were graded using the Clavien-Dindo classification. Statistical analysis and processing of the obtained data were performed using Microsoft Excel and STATISTICA10 software.Results. When comparing the gender structure of the groups, differences were not detected (p >0.05). The average age in Group I was 53.5 ± 44.4 months, in Group II — 72.0 ± 50.4 months. (p <0.01). Episodes of urinary tract infection before surgery and bilateral VUR were detected more often in patients of Group I (p <0.05). Median duration of surgery (min.) and postoperative stay (days) and quartile range [Q1; Q3] in Group I were 15 [15; 15] and 2 [2; 3], respectively, and in Group II — 100 [80; 135] and 5 [4; 7], respectively (p <0.01). After the first ET, VUR was eliminated in Subgroup I (I-III deg) in 91.7%; after the second ET, the overall efficiency increased to 92.5%. In Subgroup II (I-III deg), VUR was eliminated in all children after the first surgery (p <0.05). The formation of contralateral VUR with unilateral VUR in patients of Group I (I-III) was observed in 12.8% of cases versus 0 in Group II (I-III) (p <0.05). There were no significant differences in the frequency and severity of postoperative complications between subgroups I (I-III) and II (I-III) (p >0.05). In Subgroup I (IV-V) after the first ET, reflux was eliminated in 76.3%, after the second ET the overall efficiency was 81.4%. In Subgroup II (IV-V deg), VUR was eliminated in 100% of cases (p <0.01). When comparing the frequency of contralateral reflux formation between subgroups I (IV-V) and II (IV-V), no differences were found (p >0.05). In Subgroup I (IV-V), a predominance of the III-grade complications (p <0.01) was revealed.Conclusion. A comparative analysis of the efficacy and safety of surgical treatment of VUR using transurethral and vesicoscopic approaches revealed that ET is preferred for patients with low reflux grades (I-III). Vesicoscopic approach provides higher efficacy and safety in patients with high VUR grades (IV-V) compared with ET.